2018
DOI: 10.24275/uam/izt/dcbi/revmexingquim/2019v18n3/martinez
|View full text |Cite
|
Sign up to set email alerts
|

TIME-EFFICIENT pH-BASED METHOD TO QUANTIFY THE ACTIVITY OF ALKALINE AND HALO-ALKALINE PROTEASES

Abstract: Modelado de la biodegradación en biorreactores de lodos de hidrocarburos totales del petróleo intemperizados en suelos y sedimentos (Biodegradation modeling of sludge bioreactors of total petroleum hydrocarbons weathering in soil and sediments)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Alkaline protease with high temperature and alkaline pH optima is also desirable in detergents industry (Hang-seung and Jan, 2012). In a study protease produced from Bacillus safensis have shown optimal activity at at pH 8.0 and at 40°C and serine protease from Bacillus licheniformis showed stability at pH 7.0 (Ji et al, 2019;Shakir et al, 2019;Martínez-Pérez, 2019). In another study protease enzyme from Bacillus sp.…”
Section: Characterization Of Protease Enzymementioning
confidence: 99%
“…Alkaline protease with high temperature and alkaline pH optima is also desirable in detergents industry (Hang-seung and Jan, 2012). In a study protease produced from Bacillus safensis have shown optimal activity at at pH 8.0 and at 40°C and serine protease from Bacillus licheniformis showed stability at pH 7.0 (Ji et al, 2019;Shakir et al, 2019;Martínez-Pérez, 2019). In another study protease enzyme from Bacillus sp.…”
Section: Characterization Of Protease Enzymementioning
confidence: 99%
“…After 10min of incubation at room temperature, absorbance was recorded at 660nm using a spectrophotometer (Model: 7200 Aquarius, Cecil CE, United Kingdom). One casein degradation unit calculated as the amount of enzyme that degraded casein and release 1 µmol of tyrosine under given assay conditions (Martínez-Pérez et al, 2019).…”
Section: Enzyme Assay 241 Caseinolytic Activitymentioning
confidence: 99%